Prisotnost depresije v izbranih kritičnih poklicih v obdobju pandemije v Sloveniji - Selan, Žiga (Teorija in praksa, 2023)
The pandemic caused by the SARS-CoV-2 virus did not spare Slovenia. On the contrary, it called for a long-term and exhausting response from employees in certain critical professions. During the pandemic, noting the restrictions and need for a greater volume of work, they were exposed to a series of factors that affected their health and general well-being. In the article, we present self-assessments obtained with the help of a quantitative measurement instrument of employees in critical professions (medical personnel, police officers, members of the Slovenian Armed Forces) with regard to their feelings of stress, strain and depression during the selected period of the pandemic, between March 2020 and June 2022. The survey shows that 30% of respondents in a critical profession felt depressed. Further, the results show a correlation between depression and pandemic factors (r = .567, p = < 0.01) in all professions under study.
Keywords: Covid-19; critical professions; depresija; depression; dobrobit; kritični poklici; mental health; pandemic; pandemija; policisti; stres; Stres (psihologija); stress; vojaško osebje; zdravstveni delavci